Penderitaan Yesus di dalam Matius 27:46 dan Relasinya dengan Allah - Samuel Lengkong (Sekolah Tinggi Agama Kristen Lentera Bangsa Manado, 2024)
Abstract: When looking at the history of the teachings or understanding of Jesus or what is called christology, there are debates that occur because of the controversial understanding of the doctrine of Christ. The views of Docetism and Adoptionism both maintain on one side of Jesus himself, namely Docetism understands and defends the divinity of Jesus, while Adoptionism is more likely to understand and defend the humanity of Jesus. The aim of this research is to develop research that analyzes Jesus' humanity and His unity with God in suffering based on Matthew 27:46. The research method used by the researcher is library research. The result is that the Word is